2020
DOI: 10.3390/plants9121631
|View full text |Cite
|
Sign up to set email alerts
|

Toward the Genetic Basis and Multiple QTLs of Kernel Hardness in Wheat

Abstract: Kernel hardness is one of the most important single traits of wheat seed. It classifies wheat cultivars, determines milling quality and affects many end-use qualities. Starch granule surfaces, polar lipids, storage protein matrices and Puroindolines potentially form a four-way interaction that controls wheat kernel hardness. As a genetic factor, Puroindoline polymorphism explains over 60% of the variation in kernel hardness. However, genetic factors other than Puroindolines remain to be exploited. Over the pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 142 publications
(267 reference statements)
1
17
0
Order By: Relevance
“…Wheat is one of the most important crops worldwide, providing a food supply for about 28% of the global population [1]. However, sustaining wheat yield and quality has become unprecedentedly challenging for several reasons, including the reduction of arable land area, water resource shortages, and the emergence of new pathogens and pests.…”
Section: Introductionmentioning
confidence: 99%
“…Wheat is one of the most important crops worldwide, providing a food supply for about 28% of the global population [1]. However, sustaining wheat yield and quality has become unprecedentedly challenging for several reasons, including the reduction of arable land area, water resource shortages, and the emergence of new pathogens and pests.…”
Section: Introductionmentioning
confidence: 99%
“…All these traits mentioned above are quantitative traits. Besides the known genes, previous studies have reported numerous QTLs providing genetic basis for these traits (Groos et al, 2003;Narasimhamoorthy et al, 2006;Zhang et al, 2011;Bonneau et al, 2013;Heo and Sherman, 2013;Kumar et al, 2019;Guo et al, 2020;Tu and Li, 2020;Colasuonno et al, 2021;Fradgley et al, 2022;Gudi et al, 2022). Although epistatic QTLs, which are involved in regulatory networks, are also crucial foundations for controlling complex traits, the majority of reported loci are additive QTLs (Xing et al, 2002;Malmberg and Mauricio, 2005).…”
mentioning
confidence: 99%
“…Above all, grain protein content (GPC) has been a focus for both plant breeders and end-users since it directly affects nutritional value, and dough rheological and baking properties ( Joppa et al, 1997 ; Alamri et al, 2009 ; Brevis et al, 2010 ). GPC is a critical marketing characteristic and it influences the quality performance of wheat end products in general, including pasta and bread ( Mesfin et al, 1999 ; Distelfeld et al, 2006 ; Brevis et al, 2010 ; Naraghi et al, 2019 ) and it is used as one of the parameters for wheat classification ( Tu and Li, 2020 ). The price of wheat is also determined based on the GPC where wheat with higher GPC is valued more than lower GPC ( Farquharson, 2006 ).…”
Section: Major End-use Quality Traitsmentioning
confidence: 99%